Expression of starch-binding factor CBM20 in barley plastids controls the number of starch granules and the level of CO2 fixation - Zhong, Yingxin (Journal of experimental botany, 2020)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.